A PPy/MoS2 core–shell heterojunction modified by carbon dots exhibits high photocatalytic antibacterial performance. (26th October 2022) - Zhang, Mengmeng; Han, Sha; Niu, Xiaohui; Li, Hongxia; Zhang, Deyi; Fan, Haiyan; Liu, Xiaoyu; Wang, Kunjie
Abstract : CQDs and PPy facilitate the separation of MoS2 electron–hole pairs and enhance their photocatalytic antibacterial performance. Abstract : Developing effective antimicrobials while avoiding drug resistance remains a challenge. Using a simple in situ polymerization method, this study incorporated carbon quantum dots (CQDs) in a three-component composite PPy/MoS2 /CQD with a core–shell structure. The as-prepared composites indicated photocatalytic antibacterial activity. In the vitro antibacterial trials, a much higher bactericidal rate was achieved upon irradiation with visible light for 24 hours than under dark conditions. Moreover, the antibacterial effects of PPy/MoS2 /CQD composites indicated similar antimicrobial effects against both general and drug-resistant bacteria owing to their unique antimicrobial mechanism, wherein the core–shell structure enhances the lifetime of photo-induced electrons and holes, leading to the effective production of a large number of reactive oxygen species and inhibiting bacteria growth. In conclusion, PPy/MoS2 /CQD nanomaterials are promising antimicrobials for treating both regular and drug-resistant bacteria.